Latinas in College: Contra Viento y Marea (Against Winds and Tides) - Gabriela Díaz de Sabatés (Educational Considerations, 2007)
With the rapid demographic changes that we are experiencing in the United States in general and in the state of Kansas in particular, our educational institutions are challenged with a gigantic task: to educate a very diverse population with multifaceted linguistic and cultural backgrounds, needs, and challenges that is growing exponentially.
Keywords: class; Latinas; college; experiences; exploring; analysis; study; voices; theme